Digital Transformation Through the Go Digital MSME Application as a Sales and Service Efficiency Solution - Erly Krisnanik; Ati Zaidiah; Catur Nugrahaeni Puspita Dewi; Bambang Saras Yulistiawan; Supriyanto (Engagement: Jurnal Pengabdian Kepada Masyarakat, 2026)
Background: MSMEs in Serang Regency face significant barriers to growth, including challenges in digital marketing, inventory management, and product distribution. These operational gaps limit competitiveness and local economic development. This community service initiative addresses these issues by focusing on digital transformation through the implementation of the UMKM Go Digital System (UGODIS). Purpose of the Study: The purpose is to enhance the digital readiness and operational efficiency of MSMEs. The objectives are to improve participants' digital literacy, business management capabilities, and proficiency in online sales processes using the UGODIS platform. Methods: The program employed a learning by doing approach, which included system implementation, hands-on training, ongoing mentoring, and structured evaluation through pre-test and post-test assessments. Results: The activity resulted in significant skill improvements across all measured areas: business planning (+46%), financial management (+71%), digital marketing (+67%), online store creation (+68.5%), and real-time sales monitoring (+66%). The UGODIS system effectively enhanced MSME competitiveness, expanded market access, and contributed to building a sustainable local digital ecosystem.